Effect of binary raw materials replacement (quartz and feldspar) for porcelain chamotte on the electro-technical siliceous porcelain properties - Rodríguez, Edén A.; Díaz-Tato, Leonel; López-Perales, J. F.; González-Carranza, Yadira (Frontiers in Materials, 2023)
The hurry for ecological practices and waste control has emerged as an obligation in modern times, demanding precise strategies to restrain waste accumulation and to stimulate recycling and reuse actions to lower the climate effect. The replacement of binary raw materials for porcelain chamotte waste in siliceous porcelain was studied to obtain eco-friendly high-voltage porcelain. Quartz and feldspar were progressively replaced by 5, 10, and 15 wt.% of porcelain chamotte in a conventional siliceous electro-technical porcelain composition. The replacement effect on sintered samples at 1250°C under industrial heat treatment was evaluated by measuring the linear shrinkage, bulk density, porosity, flexural strength, and microhardness technological properties. Phase analysis was carried out by X-ray diffraction. Microstructural characteristics were studied using a scanning electron microscope. The results showed that chamotte-containing samples reached bulk densities of about 2.36 g/cm3 and a porosity percentage near zero. The maximum flexural strength value at glazed states was 87.8 MPa, for 15 wt.% scrap-containing samples. X-ray diffraction studies revealed a higher mullite phase content in chamotte-containing samples. Scanning electronic microscopy images of the polished and etched specimens show the presence of quartz grains and secondary mullite needles embedded in a feldspathic vitreous matrix. The properties reached by the chamotte-containing samples are attractive since the values obtained in terms of flexural strength, density, and porosity are compared to those reported for conventional siliceous porcelain were obtained. The most noticeable result was observed in flexural resistance. The glazed porcelain bodies showed a flexural strength improvement of about 15%. Then, these porcelain compositions suggest an alternative to produce a more sustainable, affordable, and environmentally-friendly porcelain insulator product.